Rethinking Gerontology and Geriatrics in a Nepalese Context: A Scoping Review - Sharma, Tribhuwon; Aryal, Bhagwan; Malla, Nabina (Chaturbhujeshwar Academic Journal, 2025)
Nepal’s elderly population constitutes 10.2% of the total, reflecting a rapid demographic transition, with projections estimating this will approach 14% by 2030. This scoping review systematically maps and examines gerontological and geriatric issues within Nepal by analyzing peer-reviewed literature and government reports published between 2000 and 2025. Six major thematic areas emerge: demographic transitions, policy inadequacies, rural-urban disparities, geriatric education, social security, and lessons from international models. Critical findings highlight limited access to specialist geriatric services (only 12% coverage), significant rural-urban differences, insufficient policy implementation, and minimal geriatric training in medical education (<10 hours). Traditional family-based caregiving structures are deteriorating, exposing the majority of older adults to financial insecurity and social isolation. Despite policies such as the Senior Citizens Act (2006), only 18% of the elderly population benefit from government-sponsored healthcare. Drawing on international best practices, including Japan’s Elderly Welfare Act and long-term care insurance, and the UK’s community-based eldercare and integrated training approaches, Nepal could reform its systems substantially. Urgent reforms are needed to integrate gerontology into medical curricula, expand services to rural areas, and enhance social security mechanisms. Leveraging these global experiences, Nepal can establish comprehensive coverage that safeguards the dignity and well-being of its aging population.